(untitled) (Palíndromo, 2020)
This paper takes up Hal Foster’s controversial “Design and Crime” to outline a brief historical overview of the relationship between Art Nouveau ornamentation and what the author calls “total design”. To this end, I revisit the nineteenth-century debate about ornament and explain how the cult of personality emerges with the ornamentation of public life. From this, I argue that the diffusion of design in contemporary life is linked to the behavior of the “designer of yourself”. Finally, I point out that Foster’s provocation remains current, indicating that, contrary to the narratives that expose design as the overcoming of ornament, design continues to operate largely as an ornamental rationality.